Mobile Technology Applied to the Analysis of Thermochemical Treatments - Espinosa, Milton Carlos Elías; Salcedo, Raúl Morales (Journal of Strategic Innovation and Sustainability, 2019)
In this work, the viability of the use of Mobile technologies with a digital microscope, that conducts the analysis of the growth of boride layers on AISI 12L14 steel, is evaluated. An image of the Fe2B phase from the boride layers on steel was obtained with the proposed device, later used to measure the thickness of the boride layers. A comparison of the data with images obtained using a Scanning Electron Microscope (SEM) is also conducted. In the results it can be observed how the measured thicknesses were similar and are both within the standard deviation in both cases.